A catalogação de itens de indumentária em acervos especializados em moda - PANTOJA, Dalila Monteiro (2018)
Means of an exploratory research of qualitative nature wedded to a bibliographic review and an observation research having the purpose to show how the cataloging in a fashion library occurs in information unit which is focused in fashion area. Services and products as example: clothes by subscription, tissue samples, clothes preservation and other. Is being implemented in the libraries directed to fashion, however, may not receive the care techniques necessary that can be worked the descriptive representation with appropriate manner or executed the cataloging of materials according technical norms, when the own guides of library science don’t cover such instruments to the treatment of information clearly and specifically. Concludes that the cataloging can be worked similarly the publications and documental supports treated in traditional libraries, being sufficient the knowledge and ability to handle and to adjust the features assigned to these special materials to the descriptive domain already established to traditional libraries.